EuReCa_Srbija 2014-2021 - Analysis of data on non-initiation of CPR in relation to the place of cardiac arrest - SuSkovic Bosancic, Rajka; Vasilic, Milica; Bandulaja , Marina; Medic, Sara; Ristic, Jovana (Journal Resuscitatio Balcanica, 2024)
Objective: The aim of this study was to analyze the distribution of initiation and non-initiation of cardiopulmonary resuscitation (CPR) measures across various location groups using a sample collected within the EuReCa_Serbia project. A particular focus was placed on determining how these distributions vary according to the patient’s age and the types of locations where cardiac arrest occurred. Materials and Methods: The study included epidemiological data on out-of-hospital cardiac arrest (OHCA) collected through the EuReCa study questionnaire by the European Resuscitation Council (ERC). The inclusion criterion was OHCA cases managed by the emergency medical services (EMS). The analysis included pediatric patients as well as patients with non-cardiac causes of cardiac arrest (including traumatic cardiac arrest). The database was created from information defined by the unique protocol of the EuReCa_One study from October 1, 2014, to December 31, 2021. After each questionnaire was completed, the data were entered into a unique electronic database at each research center and then into a centralized database. Results: Between October 1, 2014, and December 31, 2021, a total of 8,349 OHCA cases were recorded, of which CPR was initiated in 2,758 cases (33.1%). The analysis revealed a statistically significant difference in the frequency of initiation or non-initiation of CPR depending on specific categories of the location of the incident (χ2(8) = 847.217; p < 0.001). Additionally, a significant difference was found in the frequency of CPR initiation between cases where the cardiac arrest occurred at the patient’s residence and those outside the residence (χ2(1) = 75.319; p < 0.001). Highly statistically significant differences were also observed among different arrest locations in the group of patients older than 65 years (χ2(8) = 664.652; p < 0.001) as well as in the group of patients 65 years or younger (χ2(8) = 134.075; p < 0.001). Conclusion: The study showed that survival rates after OHCA vary depending on the location of the incident. OHCA most commonly occurs in residential settings, where outcomes are poorer due to the isolation of patients, the lack of AED devices, and a lower likelihood of a witness being present. In long-term care facilities, the high rate of non-initiation of CPR can be attributed to the age and poor health status of the patients. Conversely, public places and sports facilities offer better outcomes due to the availability of AEDs and a higher likelihood of CPR being performed. It is necessary to improve emergency response strategies in residential settings and long-term care facilities, including enhancing the availability of AEDs and training for staff.